Practical Web 2.0 Applications with PHP - Zervaa, Quentin (Springer, 2017)
Want to assert yourself as a cutting–edge PHP web developer? Take a practical approach, learning by example from author Quentin Zervaas, and discover how to bring together the many technologies needed to create a successful, modern web application.